1993
DOI: 10.1210/endo.132.2.8425491
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic profile of recombinant human (rh) inhibin A and activin A in the immature rat. II. Tissue distribution of [125I]rh-inhibin A and [125I]rh-activin A in immature female and male rats.

Abstract: The tissue distribution of recombinant human inhibin A (rh-inhibin A) and rh-activin A was determined in immature female Sprague Dawley-derived rats after iv administration of radiolabeled proteins. [125I]rh-Inhibin A and [125I]rh-activin A diverge in their distribution to tissues of the immature female rat as examined histologically (whole body autoradiography and thin section analysis) and by computing the percent dose and tissue to blood ratios for individual tissues. [125I]rh-inhibin A accumulated in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…In addition, infusion of activin A into rats caused hepatocellular necrosis around the central vein of the liver (13). These physiologic effects of activin on hepatocytes are consistent with findings that a major site of 125I-labeled activin A binding is the rat liver (14) and that the type II activin receptor is expressed in the mouse liver (ref. 15; R. Towns and M.M.M., unpublished data).…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, infusion of activin A into rats caused hepatocellular necrosis around the central vein of the liver (13). These physiologic effects of activin on hepatocytes are consistent with findings that a major site of 125I-labeled activin A binding is the rat liver (14) and that the type II activin receptor is expressed in the mouse liver (ref. 15; R. Towns and M.M.M., unpublished data).…”
Section: Introductionsupporting
confidence: 88%
“…Thus, inhibin can also function as a tumor suppressor in the adrenal cortex. Since previous studies have demonstrated that inhibin is produced in and can bind to the adrenal gland (14,(27)(28)(29) The differential temporal sensitivity of the adrenal and gonadal cells with respect to tumorigenesis is interesting. This might reflect other polypeptide hormones such as follicle-stimulating hormone or activin, which are upregulated in the absence of inhibin and may exert positive growth effects on only the gonadal cells (16,30).…”
Section: Discussionmentioning
confidence: 99%
“…In rats, unilateral ovariectomy produces a transient increase in serum FSH but not LH. After 24 hours, there is a compensatory increase in inhibin subunit mRNA levels in the follicles of the remaining ovary (D'Agostino et al, 1989). Serum FSH and inhibin B levels are highly correlated across the rat estrous cycle .…”
Section: Physiological Regulation Of Inhibin Isoformsmentioning
confidence: 99%
“…For example, iodinated inhibin A, but not iodinated activin A, binds to rat Leydig cells . In addition, the adrenal, spleen, and bone marrow bind iodinated inhibin A at much higher levels than they bind iodinated activin A (Woodruff et al, 1993a). Gonadal tumors derived from inhibin a-subunit knockout mice bind iodinated inhibin A but bind iodinated activin A at much lower levels.…”
Section: Evidence For the Existence Of An Inhibin Receptormentioning
confidence: 99%
“…There is increasing evidence suggesting that activins are not only endocrine regulators of FSH availability but also potent effectors of autocrine or paracrine intraovarian signaling. Activin receptors and downstream Smad proteins are present in rat ovaries (22)(23)(24)(25)(26), and activins apparently play important roles in regulation of folliculogenesis and follicular function (27)(28)(29)(30). However, the knowledge about granulosa cells and how they respond to Smad signaling and its regulation is still rudimentary.…”
mentioning
confidence: 99%